Social representations and meta-representations of brazilian immigrants in Europe - Rangel Batista, Roberta (2016)
Based on the theoretical contribution of the Social Representations Theory, the study aimed, to identify the social representations of Brazilians, Europeans and immigrants, in addition to the meta-representations of Brazilians and immigrants made to 180 Brazilians residing in six European countries. To do this we used a semi-structured questionnaire with free association questions for the representation of objects. The results show that Brazilians consider positively the groups of immigrants and Brazilians through affection and higher social status. The meta-representations of immigrants affirm an image of undesirability of the group on the part of Europeans; and the meta-representations of Brazilians, in turn, are oriented toward meanings that objectify Brazilian women through an image of sex and prostitution. It was concluded that the social representations – in relation to the social groups analyzed – favor the discussion of the identity function related representations, by having submitted a controversial content relating to the social groups that act as a minority against a hegemonic European society.